Expeller soybean meal as a source of rumen undegradable protein for lactating dairy cows - Shirley, John E.; Piehl, D.; Titgemeyer, Evan C.; Scheffel, Michael V. (Kansas Agricultural Experiment Station and Cooperative Extension Service, 2011)
The loss of meat and bone meal as a source of high quality protein for lactating cows creates an increased need for nonanimal sources. Fifty six Holstein cows were used to evaluate expeller soybean meal as a source of rumen undegradable intake (by-pass) protein for high producing cows. Expeller soybean meal tended to improve 3.5% contain fat-corrected milk yield and increased milk fat percentage relative to diets containing either solvent soybean meal or a meat and bone meal:blood meal mixture. In contrast, the protein percentage in milk was depressed significantly when cows were fed expeller soybean meal compared to animal protein. A limiting amino acid (possibly methionine) is implicated.
Keywords: Dairy; Lactating cows; UIP; Expeller soybean meal